RESVERATROL THERAPEUTIC POTENTIAL IN AGE-RELATED DISEASES - Tuba Demirci Yıldırım (Anti-Aging Eastern Europe)
Aging is a multifaceted biological process marked by the gradual deterioration of physiological systems, heightened susceptibility to illnesses, and eventual mortality. With the increasing proportion of older individuals worldwide, interest in strategies to decelerate aging and support healthy longevity has intensified. Resveratrol, a naturally occurring polyphenol present in grapes, berries, and various plant-derived foods, has attracted widespread attention for its potential anti-aging properties. This compound exerts its effects through multiple pathways, such as activating sirtuins, combating oxidative stress, improving mitochondrial performance, exerting anti-inflammatory effects, and protecting telomeres. Research has indicated that resveratrol can alleviate age-related conditions, including neurodegenerative diseases, cardiovascular disorders, sarcopenia, cancer, and diabetes mellitus, as evidenced by both animal studies and human clinical trials. Despite its promising potential as an anti-aging agent, further investigation is necessary to determine appropriate dosages, long-term safety, and efficacy in humans. This review provides an overview of the mechanisms underlying resveratrol’s actions, its impact on age-associated diseases, and its prospects as a therapeutic option for enhancing longevity and quality of life.